2007
DOI: 10.1016/s0140-6736(07)61865-0
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity associated with tyrosine kinase inhibitor sunitinib

Abstract: Background-Tyrosine kinase inhibitors (TKIs) have advanced cancer treatment. Sunitinib, a recently-approved, multi-targeted TKI, prolongs survival for patients with metastatic renal cell carcinoma (RCC) and gastrointestinal stromal tumor (GIST), but concerns about cardiac safety have arisen with this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

23
767
2
20

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 980 publications
(812 citation statements)
references
References 24 publications
23
767
2
20
Order By: Relevance
“…Consistent with this finding, sunitinib treatment also activated caspase-9, which is an initiator caspase of the mitochondrial apoptotic pathway, and induced apoptosis of cardiomyocytes in vitro (26). Finally, mitochondrial damage was observed in human biopsies and in mice treated with sunitinib (26). However, studies in vitro using isolated rat heart mitochondria failed to find a direct effect of sunitinib on mitochondrial function at clinically relevant concentrations (27).…”
Section: Impaired Mitochondrial Functionmentioning
confidence: 71%
See 1 more Smart Citation
“…Consistent with this finding, sunitinib treatment also activated caspase-9, which is an initiator caspase of the mitochondrial apoptotic pathway, and induced apoptosis of cardiomyocytes in vitro (26). Finally, mitochondrial damage was observed in human biopsies and in mice treated with sunitinib (26). However, studies in vitro using isolated rat heart mitochondria failed to find a direct effect of sunitinib on mitochondrial function at clinically relevant concentrations (27).…”
Section: Impaired Mitochondrial Functionmentioning
confidence: 71%
“…Preclinical experiments have shown that sunitinib treatment of cultured cardiomyocytes leads to cytochrome c release into the cytosol (26), which can activate the mitochondrial pathway for cell apoptosis. Consistent with this finding, sunitinib treatment also activated caspase-9, which is an initiator caspase of the mitochondrial apoptotic pathway, and induced apoptosis of cardiomyocytes in vitro (26). Finally, mitochondrial damage was observed in human biopsies and in mice treated with sunitinib (26).…”
Section: Impaired Mitochondrial Functionmentioning
confidence: 99%
“…28 Because of anthracycline pretreatment, special atten tion was paid to cardiac adverse events. Furthermore, cardiotoxicity is a risk with sunitinib, 29 Data are n (%).…”
Section: Discussionmentioning
confidence: 99%
“…Por ejemplo, durante la terapia con antracíclicos en adultos con linfopatía tumoral, el antecedente de HTA implicó un incremento de riesgo de insuficiencia cardíaca de 1,58 (95% IC, 1,28 a 1,95) (8) . Al mismo tiempo el desarrollo de HTA ha sido propuesto como uno de los mecanismos causales de disfunción ventricular izquierda entre los pacientes tratados con agentes inhibidores de la angiogénesis (9,10) .…”
Section: Convergencia Epidemiológicaunclassified
“…En general se utilizan como monodroga de administración oral en planes de uso prolongado, por lo que aumenta el tiempo de exposición al efecto pro hipertensivo (14) . También han sido asociadas a efecto cardiotóxico directo, que se ve potenciado por la elevación de la PA (9,14,21) .…”
Section: Modalidades De Uso De Las Drogas Inhibidoras De La Angiogénesisunclassified